2020
DOI: 10.1177/0961000619898224
|View full text |Cite
|
Sign up to set email alerts
|

What is storytime good for and what makes storytime good? A survey of public library directors

Abstract: This article reports on the findings from a nationwide survey designed to investigate the perceptions of public library directors with regard to storytime programs. The results indicate that public library directors identify a number of reasons why storytime is important; prime among those are for encouraging children’s enjoyment of books, promoting children’s early literacy skills, and attracting patrons who might otherwise not participate in library services. The findings suggest that public library director… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…It is hoped that further researchers can develop this research by using interpersonal communication theory and other visitor satisfaction theories that are the topic of discussion to be studied (17,18). And it is advisable to increase the number of reference sources in the library study, such as books or research journals (19), (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that further researchers can develop this research by using interpersonal communication theory and other visitor satisfaction theories that are the topic of discussion to be studied (17,18). And it is advisable to increase the number of reference sources in the library study, such as books or research journals (19), (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The literacy-supportive activities available at public libraries were also highlighted, and events such story-time sessions can play a key role in 'encouraging children's enjoyment of books, promoting children's early literacy skills, and attracting patrons who might otherwise not participate in library services' (Cahill et al, 2020(Cahill et al, : 1008. However, again this was a point of significant disparity between the two contexts within the sample, with UK LPs (24.3%) far more likely to value external expertise, resourcing and outreach in their LPs when compared with Australian counterparts (2.9%).…”
Section: Roles Of Librariesmentioning
confidence: 99%
“…Historically, storytime programs have been offered in public libraries since the turn of the twentieth century, when children’s libraries started to emerge (Gerber, 2014 ). According to Cahill et al ( 2020 ), storytime programs have evolved from the goal of simply sharing books for enjoyment to encompass a number of emergent skills that contribute to a child’s school readiness. In one study, Becker ( 2012 ) identified three categories of learning within the library: early literacy, learning to use the library, and other developmentally appropriate learning.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to investigate the benefits of services for young children in museums and libraries (Becker, 2012 ; Brown et al, 2018 ; Cahill et al, 2020 ; Sirinides et al, 2017 ). Sirinides et al ( 2017 ) conducted a survey of museum and library administrators and found that 96% of library administrators who responded indicated they plan to continue or expand their programs for young children in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation